2014
DOI: 10.1371/journal.pone.0098224
|View full text |Cite
|
Sign up to set email alerts
|

Postural Control Is Not Systematically Related to Reading Skills: Implications for the Assessment of Balance as a Risk Factor for Developmental Dyslexia

Abstract: Impaired postural control has been associated with poor reading skills, as well as with lower performance on measures of attention and motor control variables that frequently co-occur with reading difficulties. Measures of balance and motor control have been incorporated into several screening batteries for developmental dyslexia, but it is unclear whether the relationship between such skills and reading manifests as a behavioural continuum across the range of abilities or is restricted to groups of individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 47 publications
1
16
0
1
Order By: Relevance
“…On the contrary, our results showed no significant difference. In conclusion, the literature confirmed that the phenotype of dyslexia often encompasses many information processing deficits that extend well-beyond the phonological domain [37,48]. Previous studies have reported balance and postural deficits that are associated with dyslexia [18,23,49].…”
Section: Discussionsupporting
confidence: 64%
“…On the contrary, our results showed no significant difference. In conclusion, the literature confirmed that the phenotype of dyslexia often encompasses many information processing deficits that extend well-beyond the phonological domain [37,48]. Previous studies have reported balance and postural deficits that are associated with dyslexia [18,23,49].…”
Section: Discussionsupporting
confidence: 64%
“…The studies that confirm this influence, Loras et al 37 state, do not deal with the nature of this relationship nor explain it. Loras et al 37 find in his research that there is no statistically confirmed link between the abilities of balance and reading results on the cognitive tests or tests of attention. It should be noted that the sample consisted of 100 people aged above 20 years.…”
Section: Neuromotor Maturity and Reading Skillsmentioning
confidence: 99%
“…There are studies that explored the potential impacts of postural control on reading skills. Loras et al 37 state that there are opposing views on whether postural control affect the quality of reading. The studies that confirm this influence, Loras et al 37 state, do not deal with the nature of this relationship nor explain it.…”
Section: Neuromotor Maturity and Reading Skillsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding postural control, dyslexic children showed deteriorated performance when visual stimulus was degraded . Despite the association between reading abilities and postural control that is still controversial (Loras, Sigmundsson, Stensdotter, & Talcott, 2014;Rochelle & Talcott, 2006), poor performance in postural control in dyslexic children has been suggested to potentially be related to the manner in which sensory cues (from different sensory channels are integrated into proper motor activity (Barela, Dias, Godoi, Viana, & de Freitas, 2011). In this case, dyslexic children exhibit higher body sway and use visual cues less precisely to control body sway when compared to nondyslexic children .…”
mentioning
confidence: 99%